Franz Kafka: Sulla soglia (Balthazar, 2024)
A recurring aspect of Kafka’s “anti-heroes” is hesitation, remaining stuck on the threshold, waiting in vain to be able to gain access. This is highlighted in an exemplary way by the parable that contains the meaning of the Trial, Before the Law: the countryman waits his whole life to be able to cross the door guarded by the guardian. The other parable of Hasidic inspiration, A Message from the Emperor, also presents a similar situation, albeit inverted: the message sent by the dying emperor cannot reach the “individual”, who nevertheless awaits it confidently, the continuity of the path does not allow the messenger to reach the goal.In this impossibility of having access – to the Law, to the Truth, to existence, to birth or death, as in the case of the hunter Gracchus – we can read the condition of the foreigner of the Jew Kafka, the sense of exclusion from life developed by the authoritarian paternal upbringing, his refusal of a “normal” life – that of a public official and a husband. Many Kafkaesque characters thus live in a liminal situation, prisoners of the transition: the protagonist of The Castle waits in vain for his request to be accepted, he exhausts himself in an incessant questioning, in an interpretative effort which is a replica, in language and thought, of the inability to move and overcome obstacles.